2019
DOI: 10.1007/s00394-019-02135-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multispecies synbiotic on glucose metabolism, lipid marker, gut microbiome composition, gut permeability, and quality of life in diabesity: a randomized, double-blind, placebo-controlled pilot study

Abstract: Purpose Diabesity, the combination of obesity and type 2 diabetes, is an ever-growing global health burden. Diabesityassociated dysbiosis of the intestinal microbiome has gained attention as a potential driver of disease and, therefore, a possible therapeutic target by means of pro-or prebiotic supplementation. This study tested the effects of a multispecies synbiotic (i.e. a combination of probiotics and prebiotics) on glucose metabolism, gut microbiota, gut permeability, neutrophil function and quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 75 publications
1
61
0
6
Order By: Relevance
“…The increase of OTUs attributed to Synthrophococcus and Prevotella were correlated to a decrease in zonulin, an endogenous tight-junction regulating protein and is used as a biomarker for gut permeability, where high levels in stool or serum are indicative of a barrier dysfunction [46,47]. Decrease in zonulin levels during probiotic interventions has been shown before in obese patients with type 2 diabetes with the same product as used in the present study, and in healthy trained men with a comparable multispecies product [23,48]. Furthermore, the same product as in the presented trial showed a reduction of bacterial translocation in type 2 diabetic patients after a six month intervention and in postmenopausal women after 12 weeks [49,50].…”
Section: Discussionsupporting
confidence: 75%
“…The increase of OTUs attributed to Synthrophococcus and Prevotella were correlated to a decrease in zonulin, an endogenous tight-junction regulating protein and is used as a biomarker for gut permeability, where high levels in stool or serum are indicative of a barrier dysfunction [46,47]. Decrease in zonulin levels during probiotic interventions has been shown before in obese patients with type 2 diabetes with the same product as used in the present study, and in healthy trained men with a comparable multispecies product [23,48]. Furthermore, the same product as in the presented trial showed a reduction of bacterial translocation in type 2 diabetic patients after a six month intervention and in postmenopausal women after 12 weeks [49,50].…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, the same formulation was not effective at improving blood glycaemia in type 2 diabetes patients (Horvath et al . 2019 ). This highlights that a probiotic formulation should be designed to target a well-defined health outcome or population.…”
Section: Health-related Activities Of Lab: Evidence From Inmentioning
confidence: 99%
“…Zonulin in stool, which has been proposed to be pre-haptoglobin 2, modulates intracellular tight junctions and therefore regulates intestinal permeability [ 79 , 80 ]. It has been proven to be modifiable by microbiome targeted interventions [ 81 , 82 ]. The enzyme diamine oxidase (DAO), liable for oxidative deamination of histamine and present in the intestine from the duodenum to the ileum, inversely correlates with gut permeability of the small intestine when measured in serum and therefore represents a useful permeability marker, which is easier to obtain and store than stool samples [ 83 , 84 ].…”
Section: Gut Permeability and Bacterial Translocationmentioning
confidence: 99%